A context-specific cardiac β-catenin and GATA4 interaction influences TCF7L2 occupancy and remodels chromatin driving disease progression in the adult heart. Issue 6 (31st January 2018) - Iyer, Lavanya M; Nagarajan, Sankari; Woelfer, Monique; Schoger, Eric; Khadjeh, Sara; Zafiriou, Maria Patapia; Kari, Vijayalakshmi; Herting, Jonas; Pang, Sze Ting; Weber, Tobias; Rathjens, Franziska S; Fischer, Thomas H; et al.
Abstract: Chromatin remodelling precedes transcriptional and structural changes in heart failure. A body of work suggests roles for the developmental Wnt signalling pathway in cardiac remodelling. Hitherto, there is no evidence supporting a direct role of Wnt nuclear components in regulating chromatin landscapes in this process. We show that transcriptionally active, nuclear, phosphorylated(p)Ser675-β-catenin and TCF7L2 are upregulated in diseased murine and human cardiac ventricles. We report that inducible cardiomyocytes (CM)-specific pSer675-β-catenin accumulation mimics the disease situation by triggering TCF7L2 expression. This enhances active chromatin, characterized by increased H3K27ac and TCF7L2 occupancies to cardiac developmental and remodelling genes in vivo . Accordingly, transcriptomic analysis of β-catenin stabilized hearts shows a strong recapitulation of cardiac developmental processes like cell cycling and cytoskeletal remodelling. Mechanistically, TCF7L2 co-occupies distal genomic regions with cardiac transcription factors NKX2–5 and GATA4 in stabilized-β-catenin hearts. Validation assays revealed a previously unrecognized function of GATA4 as a cardiac repressor of the TCF7L2/β-catenin complex in vivo, thereby defining a transcriptional switch controlling disease progression. Conversely, preventing β-catenin activation post-pressure-overload results in a downregulation of these novel TCF7L2-targets and rescues cardiac function. Thus, we present a novel role for TCF7L2/β-catenin in CMs-specific chromatin modulation, which could be exploited for manipulating the ubiquitous Wnt pathway.